1998
DOI: 10.1046/j.1523-1739.1998.96085.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Avian Communities to Disturbance by an Exotic Insect in Spruce-Fir Forests of the Southern Appalachians

Abstract: The avian community of montane coniferous forests changed substantially over 21 years in response to the introduction of the balsam woolly adelgid insect ( Adelges piceae ) and the resulting death of endemic Fraser fir trees ( Abies fraseri ). These relict forests are at the southern limit of their distribution on the highest ridges of the southern Appalachian Mountains. We combined a historical study at Mount Collins in the Great Smoky Mountains with a geographic comparison of sites within five southern Appal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…These results correspond to those of Rabenold et al (1998), who found that bird species foraging mainly in the canopy showed the strongest declines following mortality of Fraser fir (Abies fraseri) caused by the balsam wooly adelgid (Adelges piceae). However, it is noteworthy that the species showing the clearest negative response to forest damage, namely the willow warbler, mainly forages for insects among the foliage of trees.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results correspond to those of Rabenold et al (1998), who found that bird species foraging mainly in the canopy showed the strongest declines following mortality of Fraser fir (Abies fraseri) caused by the balsam wooly adelgid (Adelges piceae). However, it is noteworthy that the species showing the clearest negative response to forest damage, namely the willow warbler, mainly forages for insects among the foliage of trees.…”
Section: Discussionsupporting
confidence: 90%
“…due to rapid growth of tree saplings or invasion by tall shrub species) (Bell and Whitmore 1997;Canterbury and Blockstein 1997;Rabenold et al 1998;Gale et al 2001;Becker et al 2008). This general lack of positive responses is quite surprising, since studies in other systems have repeatedly found bird species associated with open or early successional habitats to increase in forest affected by insect outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Texas, Chinese tallow (Sapium sebiferum) invades grassland partly by virtue of shading native grassland plants, and the native hackberry (Celtis laevigata) follows in its wake (Siemann and Rogers 2003). In the high elevations of the southern Appalachians, elimination of Fraser fir (Abies fraseri ) by the Asian balsam woolly adelgid (Adelges piceae) has created conditions favorable to invasion by native mountain ash (Sorbus americana) and fire cherry (Prunus pensylvanica) (Rabenold et al 1998). Finally, native ragweed (Ambrosia artemisiifolia) is favored by mound-building by the red imported fire ant (Solenopsis invicta) in South Carolina (Seaman and Marino 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance of Fraser fir forests by the balsam woolly aphid has had a detrimental effect on local birds, 10 out of 11 species declining, and six species by more than 50% (Rabenold et al 1998). Similarly, the decline of eastern hemlock due to A. tsugae in North America strongly affects bird species composition (Tingley et al 2002) and also has an effect on salamander populations (Brooks 2001), and on deer survival through modifications in forest microclimates (Lishawa et al 2007).…”
Section: Indirect Effects On Native Faunamentioning
confidence: 99%